Feeding Behavior of Toddlers from HIV/AIDS Positive Women: A Case Study in Jayapura District - Naa, Martince; Prahastuti, Brian Sri; Endarti, Ajeng Tias (LPPM Universitas Mohammad Husni Thamrin, 2025)
Background: HIV infection in pregnant women is a significant problem in the global health world because it has a serious impact on the health of the mother and the baby she is carrying. Objective: To explore the impact of HIV infection on pregnant women, particularly in the context of transmission of the virus to the baby during pregnancy and childbirth. In addition, this study also focuses on preventive measures that can be taken during pregnancy to reduce the risk of transmission of HIV from mother to baby, practice caring for the baby and giving food, looking at the mother's knowledge of transmission, which can present an evidence-based picture that can be held accountable and become an advocacy material. Methods: This study is a case study with a Qualitative approach with a specific approach of in-depth interviews. Results: This study can provide in-depth insights into the behavior of HIV mothers feeding their babies and effective preventive measures. Recommendation: There needs to be cross-sectoral cooperation to increase HIV-AIDS Education to the community, especially mothers so that it can help in improving the health of mothers and babies and reduce HIV virus transmission to generations